IMPLEMENTASI KEBIJAKAN KEIMIGRASIAN TERHADAP WARGA NEGARA ASING (WNA) DI KANTOR IMIGRASI KELAS I KHUSUS TPI SURABAYA (Studi Kasus UU No 6 Tahun 2011 Tentang Keimigrasian) - chesa Fabita Maulivi Rahmadini; Edi Suhardono (Fakultas Politik Pemerintahan IPDN, 2025)
This research aims to analyze the implementation of immigration policy towards foreign nationals (WNA) at the TPI Special Class I Immigration Office of Surabaya, based on Law Number 6 of 2011 concerning Immigration. Specifically, this study explores how the policy is applied in the supervision of foreign nationals (WNA) and identifies the supporting and inhibiting factors in the implementation process. The research employs a qualitative approach with a descriptive method to provide an in-depth overview of the immigration policy implementation. Data was collected through interviews with immigration officials and relevant parties, direct observation of procedures at the TPI Special Class I Immigration Office of Surabaya, and a study of policy documents and annual reports. The policy implementation theory of George C. Edwards III was used as the basis for analysis, considering four main variables: communication, resources, disposition, and bureaucratic structure. The results indicate that the TPI Special Class I Immigration Office of Surabaya has optimized the use of information technology and strengthened inter-agency coordination in implementing immigration policy. However, significant constraints remain, such as the limited number and competence of human resources, complex bureaucratic procedures, and a lack of synergy with labor agencies in the supervision of foreign nationals (WNA). Furthermore, the study found that cases of misuse of stay permits, such as overstay and use of unsuitable visas, are still frequent. The findings of this research provide recommendations for the government to enhance the effectiveness of immigration policy implementation through bureaucratic reform, human resource capacity building, and strengthening coordination between the Immigration Office, the Ministry of Manpower, and relevant agencies. These steps are expected to improve Indonesia's immigration system in facing the challenges of globalization and the increasing mobility of foreign nationals (WNA). Keywords: Policy Implementation, Law Number 6 of 2011, Foreign Nationals.